RECOMMENDED TIMES FOR SEXUAL INTERCOURSE: AN ANALYSIS OF QURRAH AL-UYUN BI SYARH NAZM IBN YAMUN - Muhammad Riyadi; Syibly, M. Roem (Universitas Islam Indonesia, 2024)
This study aims to describe and analyze the recommended times for sexual intercourse as outlined in the bookQurrah Al-'Uyūn bi Syarḥ Naẓm Ibni Yāmūn. A common misconception exists that the best time forintercourse is solely on Friday night due to its supposed spiritual rewards. This research, which is of the libraryresearch type, utilizes secondary data sources, primarily the book Qurrah al-'Uyūn bi Syarḥ Naẓm Ibni Yāmūnby Shaykh Abū Muhammad At-Tihāmī bin Madānī. Content analysis was employed to examine the data. Thefindings reveal that Shaykh At-Tihāmī emphasized that there is no specific time restriction for sexual intercourse,meaning it can be conducted at any time, whether day or night. Despite the permissibility of intercourse at anytime, Shaykh At-Tihāmī identifies certain preferable times, including the beginning and end of the night, Fridaynight, Monday night, and the month of Shawwal. A sahih hadith narrated by Muslim corroborates this, notingthat the Prophet married and consummated his marriage with Aisha during Shawwal. This study contributes tothe theoretical understanding of recommended times for sexual intercourse.